Development of mechanized field girth welding of high-alloy corrosion-resistant pipeline materials - Avery, Richard E.; Schillmoller, C. M. (Technical series (Nickel Development Institute (Canada)), 1992)
This paper summarize the results of a group-sponsored research program using one such system, CRC-Evans Automatic Welding, to develop high productivity welding procedures with optimum mechanical properties and corrosion resistance, depositing all passes with the pulsed gas metal arc welding, GMAW-P, process.